The Effect of Profitability, Liquidity, Solvency and Activities on The Value of Manufacturing Companies in The Food and Beverage Sub-Sector Listed on The IDX 2018-2022 - Hasanuddin, Rismayanti; Musa, Muh. Ichwan; Amin, Andi Mustika; Sahabuddin, Romansyah (PT. Maju Malaqbi Makkarana, 2023)
This research was conducted with the aim of knowing, analyzing, and testing the effect of profitability, liquidity, solvency, and activity on the value of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2018-2022 period. Profitability is measured by Return on Equity, liquidity is measured by the Current Ratio, solvency is measured by the Debt to Equity Ratio, and activity is measured by Total Asset Turnover. This study uses a type of quantitative research with a comparative causal approach. The population used in this study were 30 food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The research sample was taken using a purposive sampling technique. so that a sample of 11 food and beverage sub-sector companies were obtained which were listed on the Indonesia Stock Exchange for the 2018-2022 period. The analytical method used is multiple linear regression analysis using the SPSS version 21 program. The results of this study state that profitability has a positive and significant effect on firm value. Solvability has a positive and insignificant effect on firm value. liquidity and activity have a negative and insignificant effect on firm value.